Asʻār al-silaʻ al-ghidhāʼīyah wa-al-jawāmik fī Miṣr : aṣr dawlat al-Mamālīk al-Jarākisah : dirāsah ʻilmīyah muḥakkamah - Nabarawy, Raafat,
A Comprehensive study for the commodity prices and salaries in Egypt during the Mameluke Period.